EVALUATION OF FRESH FRUIT AND VEGETABLES LOSSES AT THE RETAIL TRADE IN MINEIROS-GO MARKET - TOFANELLI, Mauro Brasil Dias; FERNANDES, Marilaine de Sá; MARTINS FILHO, Oscar Barbosa; CARRIJO, Núbia Sousa (Scientia Agraria, 2009)
The objective of this work was to evaluate losses of fruits and vegetables on the market of the Mineiros city (Goiás State, Brazil), as well as its causes. The research was done at different retail equipments (supermarkets, groceries stores and street market) by questionnaire application from December 2005 to January 2006. The results showed week total losses of 2.9% for fruits and vegetables. Supermarkets and groceries stores losses (2.1% and 4.0%, respectively) were lower than the street market ones (15.9%). Peach (50.0%), plum (14.7%), summer squash (9.0%), papaya fruit (7.2%), nectarine (7.1%), tomato (6.2%), pineapple (6.0%) and banana (5.2%) showed medium to high rates of losses over the total volume commercialized at the different markets. The results showed that inadequate storage are the main causes of fruit and vegetable losses in the Mineiros retail trade. Although there are low losses of fruit and vegetables on the Mineiros market improvement could be done to adequate handling system and postharvest facilities to reduce that losses.